Synthesis, characterization and up-conversion photoluminescence properties of Y2O3: Er3+, Yb3+ nano-phosphors for solar cell applications - Goh, Lee Ser. (2010)
Photovoltaic solar cells can generate electricity directly from sunlight without emitting greenhouse gases. This makes it an ideal candidate as a large scale energy producer. However, the sub-bandgap loss problem of solar cells limits its efficiencies. Up-conversion mechanism could minimize this sub-bandgap loss. Thus a high efficient up-conversion material is necessary. The project aims to synthesize phosphor in nano sizes with in depth study on the factors that influence the crystal growth process and the up-conversion photoluminescence (PL).